Present and future of medical journals - Borja Ibáñez; Josep Rodés-Cabau (REC: Interventional Cardiology (English Ed.), 2019)
Access to medical literature has seen dramatic changes over the last few years. In less than two decades it has gone from a paperbased system to an online digital sending system. The advances made on computing and, above all, the Internet has revolutionized not only the way manuscripts are sent, but also how fast these get to the public (including reference manager software adaptable to the different format of various journals). This revolution has also touched the way information is being accessed these days. The databases generated at the beginning of the 21st century are «prehistoric» compared to the ones we use today. The digitalization of clinical histories and the creation of software for data mining purposes have accelerated exponentially the preparation and analysis of the data included in the studies. Even researchers have a much more transversal training and it is common to see research teams that are savvy in statistics and that facilitate data analysis. However, all these important changes are nothing compared to the actual access to general medical information. Even though access to medical literature is not actually open (something we will refer to later), access to a great deal of information is just huge. And all this has resulted in an exponential increase in the amount of papers that scientific journals receive on a monthly...